NF-κB is activated and promotes cell death in focal cerebral ischemia - Schneider, Armin; Martín-Villalba, Ana; Weih, Falk; Vogel, Johannes; Wirth, Thomas; Schwaninger, Markus (Nature medicine, 1999)
The transcription factor NF-κB is a regulator of cell death or survival. To investigate the role of NF-κB in neuronal cell death, we studied its activation in a rodent model of stroke. In the ischemic hemisphere, NF-κB was activated, as determined by increased expression of an NF-κB-driven reporter transgene, nuclear translocation of NF-κB in neurons and enhanced DNA binding of NF-κB subunits RelA and p50. In p50 knockout mice, ischemic damage was significantly reduced. This indicates a cell death-promoting role of NF-κB in focal ischemia. NF-κB may provide a new pharmacological target in neurologic disease.
Gesehen am 01.04.2021